Fluid Dynamic Simulation Studies in a Four Stroke Compression Ignition Engine - Kalivarathan, G.; Jaiganesh, V. (Asian Review of Mechanical Engineering, 2012)
Fluid Dynamic based models are always referred to “Multidimensional models”, due to their ability to provide complete geometric information on the flow field, based on the solution of the governing equations. It is well known that over the last one decade, computers were extensively used for simulation in modeling purposes and building powerful, integrated-database systems. In general, computer based simulations have been built by the theoretical foundations and it is used in a wide range of applications. Engine flow simulation normally represents turbulence to predict various types of motions of turbulence like swirl, squish, tumble and eddies. Basically turbulent flow deals with the lateral and longitudinal motion, which is due to eddy motion. Eddy is a large group of fluid particles, which moves laterally, and longitudinally in the flow field. During this type of motion, it can change its shape or stretch and rotate or breaks into two or more eddies. Eddies are generally generated in the region of high shear in the mean flow field, near the boundary in a pipe or channel flow or in the vicinity of interface between two streams flowing at different velocities and parallel to one another. The size of large eddy will be the size of flow basically or the diameter of the pipe in which flow is analyzed. The eddies of different sizes are embedded in each other and it is impermanent in nature. The larger the eddied, which are continuously formed are breaks into smaller and smaller eddies, until they are dissipated through viscous shear finally. Large Eddy Simulation is a viable option for simulating the turbulent reacting processes that occur within the diesel environment and it has high potential to represent engines unsteadiness. LES has been developed to address the largescale unsteady phenomenon and it is assumed for engine flow simulation with promising results, since it concerns the smaller part of spectrum. Normally, it is predicted that RANS can be used for preliminary design explorations, whereas LES can be used for detailed investigations. In this paper, engine flow simulation with LES is reviewed to represent the unsteady phenomenon in a diesel engine. In recent years, since the availability of high speed computing systems, the simulation techniques have become faster, easier and more accurate also. Therefore, the systems, which were upto now, not responsive for simulation techniques, have come under the purview of simulation studies. The modeling of the engine process continuous to develop as the understanding of physic sand chemistry of the phenomenon of interest steadily expands, and as the capability of the computers to solve complex equations, continues to increase.